2023
DOI: 10.3389/fnmol.2023.1237874
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing alternative splicing in Alzheimer’s disease postmortem brain: a cell-level perspective

Mohammad-Erfan Farhadieh,
Kamran Ghaedi

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease with no effective cure that attacks the brain’s cells resulting in memory loss and changes in behavior and language skills. Alternative splicing is a highly regulated process influenced by specific cell types and has been implicated in age-related disorders such as neurodegenerative diseases. A comprehensive detection of alternative splicing events (ASEs) at the cellular level in postmortem brain tissue can provide valuable insights into AD pathology. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
0
0
0
Order By: Relevance
“…A remarkable example is the gene UBC, where the linkage direction is almost completely reversed in AD compared to controls. Global alterations in splicing are increasingly appreciated in AD brains 46,[58][59][60][61] , and here we present a unique approach to identify disease-specific regulation with a small cohort size. This notion calls for expanding the current focus of identifying disease-enriched mutations to disease-specific functions of genetic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…A remarkable example is the gene UBC, where the linkage direction is almost completely reversed in AD compared to controls. Global alterations in splicing are increasingly appreciated in AD brains 46,[58][59][60][61] , and here we present a unique approach to identify disease-specific regulation with a small cohort size. This notion calls for expanding the current focus of identifying disease-enriched mutations to disease-specific functions of genetic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have revealed that changes in gene expression patterns of AD-related genes strongly impact neuronal function and neurodegeneration. In fact, activation and inactivation of transcription (Jiang et al 2013 ; Yang et al 2023 ) and translation factors (Oliveira and Klann 2022 ), expression of non-coding RNA species (Zhou et al 2019 ), alternative splicing (Biamonti et al 2021 ; Farhadieh and Ghaedi 2023 ), and epigenetic mechanisms (Sharma et al 2020 ) may play a role in the pathogenesis of AD (Bagyinszky et al 2020 ).…”
Section: Apolipoprotein E and Alzheimer’s Diseasementioning
confidence: 99%